Islamophobia in Britain: Causes and Effects - Soltani, Chaima (جامعة الوادي University of Eloued, 2019)
ﺗﺸﮭﺪ ظﺎھﺮة اﻹﺳﻼﻣﻮﻓﻮﺑﯿﺎ ﺗﺰاﯾﺪا ﻛﺒﯿﺮا ﻓﻲ اﻟﻌﺎﻟﻢ أﺟﻤﻊ و ﺧﺎﺻﺔ ﺑﺮﯾﻄﺎﻧﯿﺎ. ﺣﯿﺚ أﺻﺒﺢ اﻹﺳﻼم ﻣﻔﮭﻮﻣﺎ ﯾﺮﻣﺰ ﻟﻺرھﺎب، و ﻣﺮﺗﺒﻄﺎ ﺑﻮﺟﮭﺎت ﻧﻈﺮ ﺳﻠﺒﯿﺔ ﺗﺠﺎه اﻹﺳﻼم و اﻟﻤﺴﻠﻤﯿﻦ ﻋﻠﻰ وﺟﮫ اﻟﺨﺼﻮص .اﻧﻄﻼﻗﺎ ﻣﻦ اﻋﺘﺒﺎر و ﺗﻘﺼﻲ ﻣﺪى ﺗﺄﺛﯿﺮھﺎ ﻋﻠﻰ ، ﺗﮭﺪف ھه اﻟﺪراﺳﺔ إﻟﻰ ﺗﻮﺿﯿﺢ و ﺗﺤﻠﯿﻞ أﺳﺒﺎﺑﮭﺎ ، اﻹﺳﻼﻣﻮﻓﻮﺑﯿﺎ ظﺎھﺮة ﺣﻘﯿﻘﯿﺔ ﺻﻮرة اﻹﺳﻼم و اﻟﻤﺴﻠﻤﯿﻦ ﻓﻲ ﺑﺮﯾﻄﺎﻧﯿﺎ .ﻛﻤﺎ ﺗﺴﻌﻰ إﻟﻲ ٳﺛﺒﺎت ﺣﻘﯿﻘﺔ وﺟﻮدھﺎ ﻓﻲ اﻟﻤﺠﺘﻤﻊ اﻟﺒﺮﯾﻄﺎﻧﻲ .وﺑﻐﯿﺔ ﺑﻠﻮغ ھه اﻷھﺪاف، اﻋﺘﻤﺪ اﻟﺒﺤﺚ ﻋﻠﻰ اﻟﻤﻨﮭﺞ اﻟﻮﺻﻔﻲ ﺑﺘﻘﺪﯾﻢ ﺗﻌﺮﯾﻔﺎت وﺷﺮوح ﻣﺘﻀﻤﻨﺔ ﻓﻲ اﻟﻔﺼﻞ اﻷول و اﻟﺜﺎﻧﻲ ، إﺿﺎﻓﺔ إﻟﻰ اﻟﻤﻨﮭﺞ اﻟﺘﺎرﯾﺨﻲ ﻓﻲ اﻟﻔﺼﻞ اﻟﺜﺎﻟﺚ اﻟﻤﻌﺘﻤﺪ ﻓﻲ ﺗﻘﺼﻲ اﻟﺴﯿﺎﺳﺎت اﻟﺤﻜﻮﻣﯿﺔ و اﻟﻤﻤﺎرﺳﺎت اﻟﺴﯿﺎﺳﯿﺔ ﻣﻦ واﻗﻊ اﻟﻤﺠﺘﻤﻊ اﻟﺒﺮﯾﻄﺎﻧﻲ .و ﻗﺪ أظﮭﺮت اﻟﺪراﺳﺔ ٲن ﻟﻺﺳﻼﻣﻮﻓﻮﺑﯿﺎ ٲﺳﺒﺎﺑﺎ ﻣﺘﻌﺪدة وﻣﺨﺘﻠﻔﺔ و أﺛﺎرا واﺿﺤﺔ و ﺟﻠﯿﺔ ﻣﻤﺎ ﯾﺆﻛﺪ ﺣﻘﯿﻘﺔ وﺟﻮدھﺎ ﻓﻲ ﺑﺮﯾﻄﺎﻧﯿﺎ. Islamophobia is a phenomenon that witnessed a rise in the entire world, particularly in Britain and that is linked with negative perspectives and prejudices against either Muslims or Islam, in which the latter is viewed to be the notion of terrorism. This dissertation examines the causes and the effects of Islamophobia in Britain. Through the existence of numerous causes and effects and by considering Islamophobia as a real phenomenon in Britain, this study aims at clarifying and assessing the causes and pointing out the effects. For that, there is a need to complete the missed gaps and to affirm the existence of Islamophobia to the sides who are denying it, and to raise awareness about the incentives of this phenomenon in Britain. To achieve the objectives of this dissertation, the descriptive and the historical methods are used. The study reveals that Islamophobia has numerous causes and effects which emphasizes the real existence of Islamophobia in Britain.
Keywords: Britain, Causes and effects of Islamophobia, Islam, Islamophobia, Muslims; ا أﺳﺒﺎب و ﻧﺘﺎﺋﺞ ﻹ ﺑﺮﯾﻄﺎﻧﯿﺎ ̦ ، ،اﺳﻼﻣﻮﻓﻮﺑﯿﺎ ،ﺳﻼﻣﻮﻓﻮﺑﯿﺎ ،اﻹﺳﻼم اﻟﻤﺴﻠﻤﯿﻦ